Study of Socio-Demographic Factors in Cases of Pregnancy Induced Hypertension and its Associated Risk Factors in One of Tertiary Care Hospitals of South Punjab - Sanober Qadeer, Uzma Arshad, Ayesha Saddique, Qaiser Jehangir Khan, Abeer Zahra, Hareem Malik, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To get the risk factors and sociodemographic profile of prenatal females who had pregnancy induced hypertension. Methods: The current retrospective study was carried out Multan Medical and Dental College, Multan from 2023 to 2024 in the obstetrics and gynecology department. 76 cases of PIH-affected pregnant women in total were examined. From the hospital records, sociodemographic information such as age, parity, gestational age of presentation, mode of birth, and maternal and perinatal problems were noted and examined. Results: Instances of PIH were observed to affect 7.19% of pregnant patients who came to the Hospital. 67% percent of the research participants were from rural areas. Women without formal education had a greater frequency of PIH (52.45%). 28% of cases were in the 17–24 age range, while 52.98% of cases were in the 25–29 age range. According to the current study, primigravidas had a higher incidence of PIH (62.49%) than multigravidas (31.5%). 25.25% of cases were delivered vaginally, whereas 71.45% of cases were delivered by caesarean section. Of the 80 cases, eclampsia complicated 14.25% of cases, severe PIH complicated 11.5%, abruption placentae complicated 2.9%. Conclusions: A very frequent pregnancy condition PIH linked to unfavorable results for either, the mother and the fetus. Rural populations and young primigravidas are more at danger. Reducing the incidence of PIH and its related consequences will be made easier with improved healthcare facilities and more awareness among expectant mothers. Keywords: Hypertension induced in pregnancy, Eclampsia, Primigravida, Gestational age.